2012
DOI: 10.1016/j.juro.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin Based Induction Chemotherapy for Nonorgan Confined Bladder Cancer—A Reasonable Alternative for Cisplatin Unfit Patients?

Abstract: Induction gemcitabine and carboplatin for nonorgan confined urothelial carcinoma achieves clinical and pathological response rates, and survival outcomes comparable to those of the cisplatin based combination chemotherapy schemes. Our data suggest that a carboplatin based regimen can be considered a reasonable alternative for cisplatin unfit patients in the preoperative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It is important to recognize such subgroups because study findings may be influenced by these; however, even if the four patients who had clinically progressive disease are considered to have pathologically tumour‐positive LNs, the difference in incidence of occult LN metastases between the NAC and the non‐NAC group among the patients with cT3–4 disease, remains significant (NAC: 26.0% vs non‐NAC: 40.7%, P = 0.012). Another weakness was the use of three different chemotherapeutic regimens; however, a previous report from our group showed similar pathological response rates .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is important to recognize such subgroups because study findings may be influenced by these; however, even if the four patients who had clinically progressive disease are considered to have pathologically tumour‐positive LNs, the difference in incidence of occult LN metastases between the NAC and the non‐NAC group among the patients with cT3–4 disease, remains significant (NAC: 26.0% vs non‐NAC: 40.7%, P = 0.012). Another weakness was the use of three different chemotherapeutic regimens; however, a previous report from our group showed similar pathological response rates .…”
Section: Discussionmentioning
confidence: 78%
“…, or gemcitabine/cisplatin (gemcitabine 1000–1250 mg/m 2 and cisplatin 70 mg/m 2 on day 1 in 4 h, gemcitabine 1000 mg/m 2 on day 8 in 30 min) in a 21‐day cycle. Patients who were considered unfit for cisplatin were selected to receive carboplatin‐based combination chemotherapy; gemcitabine/carboplatin . Selection criteria correspond to those described by Galsky et al.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in a small comparative series by Mertens et al [36], the rate of pCR for patients with non–organ-confined BCa receiving CaG was 30.4%. The authors concluded that CaG might be a reasonable alternative to cisplatin in unfit patients.…”
Section: Discussionmentioning
confidence: 86%
“…Patients were treated with different platinumcontaining chemotherapy regimens: MVAC (methotrexate, vinblastine, doxorubicin, and cisplatin), gemcitabine and cisplatin, or gemcitabine and carboplatin. Although evidence for the benefit of gemcitabine and carboplatin in the neoadjuvant setting in terms of cancer-specific or overall survival is lacking, pathologic complete response rates appear to be similar [8]. Our cohort also contained more advanced cases than most neoadjuvant studies in bladder cancer.…”
mentioning
confidence: 98%